Preparation method and application of electrochemical gas sensor with porous ceramic substrate
By adopting porous ceramic substrates and hydrophobic modification technology, the problem of electrochemical gas sensors' response time affected and zero-point drift when humidity changes is changed is solved, which achieves higher stability and service life and reduces production costs.
Patent Information
- Application Number
- CN202411915231.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The response time of existing electrochemical gas sensors is affected when humidity changes, and there is a problem of zero point drift, resulting in a short life.
The porous ceramic substrate was used to synthesize Fe and Mn composite Al2O3 ceramic powder by ball milling, pressed into porous ceramic embryo sheets and fired. Combined with hydrophobic agent modification treatment, the hydrophobic breathability of the substrate was improved, and electrodes were formed by platinum slurry printing and sintering. Finally, a proton exchange membrane was formed using a nafion solution and a catalyst.
It improves the stability and service life of electrochemical sensors, reduces production costs, solves the problem of zero-point drift, and enhances the selectivity and responsiveness to gases.
Smart Images

Figure CN119730038A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical gas sensors, and in particular to a preparation method and application of a porous ceramic substrate electrochemical gas sensor. Background Art
[0002] The basic structure of an electrochemical gas sensor includes diffusion holes, dust-proof membranes, electrode membranes, working electrodes, reference electrodes, counter electrodes, electrolytes, and packaging shells. Nowadays, commercial electrochemical gas sensors commonly found on the market mostly use ceramic substrates such as Al2O3 (aluminum oxide) and YSZ (yttrium stabilized zirconia), and are usually designed in a sheet-type structure. Typical representatives of this type of sensor include the ES1-AG1-10000 All Gas gas sensor developed by EC Sense of Germany, which uses an alumina ceramic substrate and laser punches holes on the back of the substrate to form gas diffusion holes, so that the target gas reaches the electrode surface for electrochemical oxidation and reduction reactions. In addition, the patent (CN117665069 A) discloses an electrochemical gas sensor, which uses an electrochemical corrosion method to form a porous structure on the working electrode, ultimately increasing the intensity of the sensing current density and enhancing its performance.
[0003] Humidity is one of the factors that have a great impact on the life of existing electrochemical gas sensors. The ideal working condition of electrochemical gas sensors is 20%-60% relative humidity. Low ambient humidity will cause the internal electrolyte to dry out, thus affecting the response time. On the other hand, high relative humidity will cause electrolyte dilution, affecting sensor performance and even leading to pin corrosion. In addition, existing electrochemical gas sensors have zero drift problems, which causes the sensors to need to be replaced frequently and have a short lifespan. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a porous ceramic substrate electrochemical gas sensor, which changes the original electrochemical gas sensor packaging form, and the ceramic substrate has a hydrophobic and breathable function in addition to a high-strength structure, which greatly improves the stability and service life of the electrochemical sensor and reduces the production cost.
[0005] In one aspect of the present invention, the present invention provides a method for preparing a porous ceramic substrate electrochemical gas sensor. According to an embodiment of the present invention, the method comprises the following steps:
[0006] (1) Alumina, starch and deionized water are mixed and ball-milled, and then MnO, Fe2O3, methyl cellulose and a dispersant are added and ball-milled for further processing, and the slurry obtained by ball milling is dried, ground and sieved to obtain a uniform Fe, Mn composite Al2O3 ceramic powder;
[0007] (2) pressing Fe, Mn composite Al2O3 ceramic powder into a porous ceramic green sheet, and then firing it to obtain a porous FeMn@Al2O3 ceramic substrate;
[0008] (3) grinding and washing the FeMn@Al2O3 ceramic substrate, then printing platinum slurry on the FeMn@Al2O3 ceramic substrate, and sintering to obtain a porous electrochemical gas sensor substrate;
[0009] (4) The porous electrochemical gas sensor substrate is modified by infiltrating with a hydrophobic agent solution and then dried, and the catalyst slurry is spot-coated on the working electrode and the counter electrode on the modified porous electrochemical gas sensor substrate. After drying, the pretreated Nafion solution is evenly coated on the surface of the working electrode and the counter electrode, and dried and solidified to form a proton exchange membrane. A dilute sulfuric acid solution is spot-coated on the proton exchange membrane, and finally, the entire electrode side is sealed with silica sol to obtain the porous ceramic substrate electrochemical gas sensor.
[0010] In addition, the method for preparing a porous ceramic substrate electrochemical gas sensor according to the above embodiment of the present invention may also have the following additional technical features:
[0011] In some embodiments of the present invention, in step (1): the mass ratio of alumina to starch is (3.8:1)-(4:1), the mass ratio of MnO to Fe2O3 is (1:1)-(1.5:1), methyl cellulose is 0.1 g, and the dispersant is 50-150 μ; the second ball milling time is 3-5 h, the rotation speed is 700-800 r / min; the sieve is 80-100 mesh.
[0012] In some embodiments of the present invention, in step (2): the pressing pressure is 10-22T, and the pressing time is 1-5min; the porous ceramic green sheet is round, with a diameter of 6-7cm and a thickness of 1-3mm; the firing parameters are as follows: 0-500℃ heating rate is 2-3℃ / min, 500℃ insulation for 100-120min, continue to heat to 1400-1500℃ and insulation for 100-120min, and then cool to room temperature.
[0013] In some embodiments of the present invention, in step (3): the polishing is performed using sandpaper; the cleaning is performed using 5wt%-15wt% dilute sulfuric acid and deionized water to wash away excess impurities and organic residues to facilitate subsequent modification treatment; the printing is performed using screen printing technology, and the screen printing mesh is 450-480 mesh; the sintering temperature is 800-900°C, the sintering time is 30-45min, and the heating rate is 2-5°C / min.
[0014] In some embodiments of the present invention, in step (4), the hydrophobic agent includes one or more of methyltriethoxysilane, polytetrafluoroethylene (PTFE), perfluorooctyltriethoxysilane (FAS-17), palmitic acid, ethyl acetate, and polyvinyl alcohol, and the mass percentage thereof is 60%-80%, and the infiltration time is 24-48h; the drying temperature after the infiltration treatment is 80-120°C, and the drying time is 0.5-1.5h.
[0015] In some embodiments of the present invention, in step (4), the catalyst slurry includes a Pt / C catalyst and one or more of isopropanol, water, ethylene glycol, polyethylene glycol, glycerol, nafion, PVA, and methyl cellulose; the drying temperature after the spot coating is 100-140°C, and the drying time is 4-5h.
[0016] In some embodiments of the present invention, in step (4), the nafion solution pretreatment method is as follows: the nafion solution is mixed with one of glycerol, ethylene glycol, ionic liquid, neopentyl glycol ester, and DMF in a volume ratio of 1:1 to obtain a pretreated nafion solution. By introducing a plasticizer that can improve the adhesion between nafion and the porous ceramic substrate, the film forming property is improved. In addition, these plasticizers can reduce the amount of nafion used and reduce costs.
[0017] In another aspect of the present invention, the present invention provides a porous ceramic substrate electrochemical gas sensor prepared according to the method for preparing a porous ceramic substrate electrochemical gas sensor.
[0018] In another aspect of the present invention, the present invention proposes the use of the porous ceramic substrate electrochemical gas sensor in detecting hydrogen.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention reduces the ceramic sintering temperature and improves the strength and flatness of the ceramic sheet by adding Fe2O3 and MnO for ball milling, which is beneficial to electrode printing. In addition, the introduced Fe and Mn metals can improve the corrosion resistance of the substrate and improve the stability and long-term life of the sensor.
[0021] (2) The present invention adds corn starch to make the final porosity of the ceramic substrate appropriate, which meets the air permeability requirements and facilitates the subsequent hydrophobic modification treatment; by adding a dispersant, the friction coefficient between the material particles is reduced, the ball milling efficiency and the blank forming performance are improved; by sieving the ceramic powder, the ceramic powder particles are made uniform, which is convenient for subsequent tableting operations and conducive to sintering.
[0022] (3) The present invention treats the ceramic substrate with dilute sulfuric acid and sintering at 900° C., which is beneficial to the solidification and bonding between the Pt electrode and the porous substrate, thereby improving the reliability of the electrode.
[0023] (4) The present invention improves the surface hydrophobicity of the porous ceramic substrate by modifying the porous ceramic substrate with 60wt%-80wt% hydrophobic agent, while preventing internal liquid leakage and ensuring the long-term stability of the sensor.
[0024] (5) In the present invention, a certain proportion of plasticizer is mixed into Nafion to improve its adhesion to the porous substrate during the film forming process, while avoiding the proton transmission capacity being affected.
[0025] (6) The electrochemical gas sensor based on the FeMn@Al2O3 porous ceramic substrate designed in the present invention has the advantages of good selectivity, high stability, simple preparation, low cost, strong adaptability and environmental friendliness.
[0026] (7) The present invention improves the bonding strength between the current collector Pt and the porous substrate, sintering the Pt electrode at high temperature, removing impurities and organic matter, and reducing its own resistance. In addition, the hydrophobic modification technology of the porous substrate will also greatly improve the stability of the sensor, reduce humidity and particulate matter in the environment, and interfere with the influence of gas, thereby solving the zero drift problem existing in existing electrochemical gas sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A top view of the screen-printed electrode in Example 1 of the present invention, in which 1 is the platinum paste after screen printing, the remaining shaded parts are also platinum paste, and 2 is a circular porous ceramic substrate;
[0028] Figure 2 A schematic diagram of the structure of a porous electrochemical gas sensor substrate prepared in step 3 of Example 1 of the present invention, in which 3 is a working electrode, 4 is a reference electrode, 5 is a counter electrode, and 6 is a lead;
[0029] Figure 3 A hydrophobicity test diagram of the porous electrochemical gas sensor substrate prepared in step 3 of Example 1 of the present invention;
[0030] Figure 4 A welding strength test diagram of the porous electrochemical gas sensor substrate prepared in step 3 of Example 1 of the present invention;
[0031] Figure 5 Resistance test graph of the porous electrochemical gas sensor substrate prepared in step 3 of Example 1 of the present invention;
[0032] Figure 6 The sintering curve of the circular porous ceramic green sheet prepared in step 2 of Example 1 of the present invention;
[0033] Figure 7 A physical picture of the porous ceramic substrate electrochemical gas sensor prepared in Example 1 of the present invention;
[0034] Figure 8 Sensitivity test diagram of the porous ceramic substrate electrochemical gas sensor prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] A method for preparing a porous ceramic substrate electrochemical gas sensor comprises the following steps:
[0038] Step 1: Preparation of FeMn@Al2O3 ceramic materials
[0039] Use an analytical balance to weigh 5.5g of aluminum oxide and 1.4g of starch in an agate ball mill. Use a measuring cylinder to measure 25ml of deionized water and pour it into the ball mill. Mill for 30 minutes to allow the powder to be fully mixed and then stop milling. Continue to use an analytical balance to weigh 0.5g of MnO, Fe2O3 and 0.1g of methyl cellulose and add them to the ball mill. Use a pipette to draw 150μL of dispersant (where the volume ratio of glycerol to PEG 400 is 2:1) and add it to the ball mill. Put the ball mill into a ball mill and mill for 3h, setting the speed to 800r / min. Take out the milled slurry and pour it into a 100ml beaker, rinse the residual slurry with an appropriate amount of deionized water, and pour it into the beaker. Put the slurry in a blast drying oven, set to 80℃, and dry it for 10h. The dried powder is taken out, ground and sieved in sequence, and the sieve is selected to be 80 mesh, so as to obtain a uniform Fe, Mn composite Al2O3 ceramic powder.
[0040] Step 2: Preparation of FeMn@Al2O3 porous ceramic substrate
[0041] Use a balance to weigh 3.2g of the Fe, Mn composite Al2O3 ceramic powder in a mold, use a flattener to spread the powder in the mold, put the mold into a hydraulic press, keep it at 22T pressure for 5min, and demould to obtain a circular porous ceramic embryo with a diameter of 6.5cm and a thickness of 2mm. Figure 6The porous FeMn@Al2O3 ceramic substrate can be obtained by sintering according to the sintering curve shown in the figure (0-500℃ heating rate is 2℃ / min, 500℃ is kept for 120min, the temperature is further increased to 1500℃ and kept for 120min, and then cooled to room temperature). Figure 6 As shown, when the temperature is raised to 500°C, it is kept warm for 2 hours to facilitate the volatilization of organic matter, remove pollutants and release internal stress, ensure the flatness and integrity of the substrate, and facilitate the subsequent printing of electrodes and preparation of electrochemical sensors.
[0042] Step 3: Preparation of porous electrochemical gas sensor substrate
[0043] First, the surface of the ceramic substrate is polished with sandpaper to make it smooth and flat, and then the surface is treated with 5wt% dilute sulfuric acid and deionized water in turn to wash away excess impurities and organic residues for subsequent modification. Figure 1 As shown in the figure, the commercially available PE-pt-7840 (Guiyan Platinum Co., Ltd.) platinum paste is printed on the circuit by screen printing technology, the screen printing mesh size is 460 mesh, and the ceramic sheet after printing the platinum paste is sintered at 900 degrees (heating rate 2°C / min) to make the platinum paste sintered into platinum electrodes and solidified on the ceramic sheet. After cutting and edge grinding, a porous electrochemical gas sensor substrate can be obtained, as shown in the figure. Figure 2 As shown, the size of the porous electrochemical gas sensor substrate after cutting is 10.5 mm*10.5 mm and the thickness is 0.9 mm.
[0044] Step 4: Preparation of electrochemical gas sensor on porous ceramic substrate
[0045] The porous electrochemical gas sensor substrate prepared in step 3 was modified and treated by using a 60wt% mixed solution of FAS-17 and ethyl acetate as a hydrophobic agent to infiltrate the porous ceramic substrate for 48h, and then dried at 80°C. 0.2g of Pt / C catalyst was mixed with 50μL of isopropanol, 10μL of nafion and 0.02g of methyl cellulose to prepare a catalyst slurry, and the catalyst slurry was spot-coated on the working electrode and the counter electrode on the ceramic substrate. Figure 2 3 and 5 positions on it. After the spot coating is completed, it is placed in an oven and dried at 120°C for 5 hours. The pretreated nafion (nafion and glycerol are mixed in a volume ratio of 1:1) solution is evenly coated on the electrode surface and placed in a drying oven at 150°C for 20 minutes to solidify it on the surface of the porous ceramic substrate to form a proton exchange membrane. 5μL of 0.1M dilute sulfuric acid solution is spot coated on the solidified nafion membrane. Finally, one side of the electrode is sealed with silica sol to obtain an electrochemical gas sensor based on a FeMn@Al2O3 porous ceramic substrate.
[0046] The hydrophobicity test of the porous electrochemical gas sensor substrate prepared in step 3 is performed, such as Figure 3 As shown, by adding water droplets to the surface, the angle between the droplets and the surface is tested, that is, the measured hydrophobic angle θ is 120°, which is significantly greater than 90°. The surface material has good hydrophobicity.
[0047] The porous electrochemical gas sensor substrate prepared in step 3 was subjected to a welding strength test. A small amount of solder paste was applied on the electrode surface, and the temperature of the hot air gun was adjusted to 350°C to purge the surface. Figure 4 As shown, the pins are soldered, with solder balls attached to the surface, which is firmly bonded, and the Pt electrodes on the substrate surface do not fall off, ensuring the mass production and reliability of the sensor.
[0048] The resistance test of the reference electrode-pin end of the porous electrochemical gas sensor substrate prepared in step 3 was 2.4Ω, and the surface circuit of the surface ceramic substrate was conductive. In addition, the resistance values of the working electrode-pin end and the counter electrode-pin end were tested respectively. The test results were consistent with Figure 5 The results are consistent.
[0049] like Figure 7 As shown, from top to bottom are silica sol sealing layer, dilute sulfuric acid solution (trace amount), nafion membrane, Pt / C catalyst, hydrophobic layer, Pt electrode, FeMn@Al2O3 porous ceramic substrate and hydrophobic layer.
[0050] The sensitivity test of the porous ceramic substrate electrochemical gas sensor was carried out. During the test, the sensor lead was connected to the electrochemical workstation and sealed in a closed cavity. 50 ml of standard gas (hydrogen and air mixture, concentration of 2%) was drawn from the standard gas bag through a needle and injected into the cavity. Multiple injections increased the concentration in the cavity cumulatively, forming a current step response diagram. Figure 7 As shown, the porous ceramic substrate electrochemical gas sensor is tested for H2 sensitivity, and the response current value at 480ppm reaches 1500nA.
[0051] Example 2
[0052] A method for preparing an electrochemical gas sensor on a porous ceramic substrate. The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of MnO to Fe2O3 is 1:3, and the remaining steps and parameters are the same as those in embodiment 1.
[0053] Example 3
[0054] A method for preparing an electrochemical gas sensor on a porous ceramic substrate. The difference between this embodiment and embodiment 1 is that in step 1, the mass ratio of MnO to Fe2O3 is 3:1, and the remaining steps and parameters are the same as those in embodiment 1.
[0055] Example 4
[0056] A method for preparing an electrochemical gas sensor on a porous ceramic substrate. The difference between this embodiment and embodiment 1 is that in step 1, the dispersant is ethylene glycol and PEG 600 in a volume ratio of 2:1, and the remaining steps and parameters are the same as those in embodiment 1.
[0057] Example 5
[0058] A method for preparing a porous ceramic substrate electrochemical gas sensor, the difference between this embodiment and embodiment 1 is that: in step 2, 3.5g of Fe, Mn composite Al2O3 ceramic powder is weighed and pressed, and the remaining steps and parameters are the same as those in embodiment 1. The thickness of the final green sheet is too thick, 2mm, resulting in poor permeability and poor sensor response.
[0059] Example 6
[0060] A method for preparing an electrochemical gas sensor on a porous ceramic substrate. The difference between this embodiment and embodiment 1 is that in step 3, 15wt% dilute sulfuric acid is used to treat the surface of the ceramic substrate, and the remaining steps and parameters are the same as those in embodiment 1.
[0061] Example 7
[0062] A method for preparing an electrochemical gas sensor on a porous ceramic substrate. The difference between this embodiment and embodiment 1 is only that: in step 4, a 60wt% mixed solution of FAS-17 and ethyl acetate is used as a hydrophobic agent to infiltrate the porous ceramic substrate for 6 hours, and the remaining steps and parameters are the same as those in embodiment 1.
[0063] Example 8
[0064] A method for preparing an electrochemical gas sensor on a porous ceramic substrate. The difference between this embodiment and embodiment 1 is only that: in step 4, a 60wt% mixed solution of FAS-17 and ethyl acetate is used as a hydrophobic agent to infiltrate the porous ceramic substrate for 12 hours, and the remaining steps and parameters are the same as those in embodiment 1.
[0065] Example 9
[0066] A method for preparing an electrochemical gas sensor on a porous ceramic substrate. The difference between this embodiment and embodiment 1 is only that: in step 4, a 60wt% mixed solution of FAS-17 and ethyl acetate is used as a hydrophobic agent to infiltrate the porous ceramic substrate for 24 hours, and the remaining steps and parameters are the same as those in embodiment 1.
[0067] Example 10
[0068] A method for preparing an electrochemical gas sensor on a porous ceramic substrate. The difference between this embodiment and embodiment 1 is only that: in step 4, 60wt% PTFE emulsion is used as a hydrophobic agent to infiltrate the porous ceramic substrate for 48 hours, and the remaining steps and parameters are the same as those in embodiment 1.
[0069] Embodiment 11
[0070] A method for preparing an electrochemical gas sensor on a porous ceramic substrate. The difference between this embodiment and embodiment 1 is that in step 4, 0.2 g of Pt / C catalyst is mixed with 50 μL PEG400 and 10 μL nafion to prepare a catalyst slurry, and the remaining steps and parameters are the same as those in embodiment 1.
[0071] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing an electrochemical gas sensor on a porous ceramic substrate, characterized in that: The following steps are involved: (1) Alumina, starch and deionized water are mixed and ball-milled, and then MnO, Fe2O3, methyl cellulose and a dispersant are added and ball-milled for further processing, and the slurry obtained by ball milling is dried, ground and sieved to obtain a uniform Fe, Mn composite Al2O3 ceramic powder; (2) pressing Fe, Mn composite Al2O3 ceramic powder into a porous ceramic green sheet, and then firing it to obtain a porous FeMn@Al2O3 ceramic substrate; (3) grinding and washing the FeMn@Al2O3 ceramic substrate, then printing platinum slurry on the FeMn@Al2O3 ceramic substrate, and sintering to obtain a porous electrochemical gas sensor substrate; (4) The porous electrochemical gas sensor substrate is modified by infiltrating with a hydrophobic agent solution and then dried, and the catalyst slurry is spot-coated on the working electrode and the counter electrode on the modified porous electrochemical gas sensor substrate. After drying, the pretreated Nafion solution is evenly coated on the surface of the working and counter electrodes, and dried and solidified to form a proton exchange membrane. A dilute sulfuric acid solution is spot-coated on the proton exchange membrane, and finally, the entire electrode side is sealed with silica sol to obtain the porous ceramic substrate electrochemical gas sensor.
2. The method for preparing a porous ceramic substrate electrochemical gas sensor according to claim 1, characterized in that: In step (1): The mass ratio of aluminum oxide to starch is (3.8:1)-(4:1), and the mass ratio of MnO to Fe2O3 is (1:1)-(1.5:1); The second ball milling time is 3-5h, and the speed is 700-800r / min; The sieve used is 80-100 mesh.
3. The method for preparing a porous ceramic substrate electrochemical gas sensor according to claim 1, characterized in that: In step (2): The pressing pressure is 10-22T, and the pressing time is 1-5min; The porous ceramic green sheet is round, with a diameter of 6-7 cm and a thickness of 1-3 mm; The firing parameters are as follows: a heating rate of 2-3°C / min from 0 to 500°C, keeping at 500°C for 100-120min, continuing to heat to 1400-1500°C and keeping for 100-120min, and then cooling to room temperature.
4. The method for preparing a porous ceramic substrate electrochemical gas sensor according to claim 1, characterized in that: In step (3): The grinding is performed using sandpaper; The cleaning is carried out using 5wt%-15wt% dilute sulfuric acid and deionized water; The printing adopts screen printing technology, and the screen printing mesh is 450-480 meshes; The sintering temperature is 800-900°C, the sintering time is 30-45min, and the heating rate is 2-5°C / min.
5. The method for preparing a porous ceramic substrate electrochemical gas sensor according to claim 1, characterized in that: In step (4), the hydrophobic agent solution includes one or more of methyltriethoxysilane, polytetrafluoroethylene, perfluorooctyltriethoxysilane, palmitic acid, ethyl acetate, and polyvinyl alcohol, with a mass percentage of 60%-80%, and the infiltration time is 24-48h; the drying temperature after the infiltration treatment is 80-120°C, and the drying time is 0.5-1.5h.
6. The method for preparing a porous ceramic substrate electrochemical gas sensor according to claim 1, characterized in that: In step (4), the catalyst slurry includes Pt / C catalyst and one or more of isopropanol, water, ethylene glycol, polyethylene glycol, glycerol, nafion, PVA, and methyl cellulose; the drying temperature after the spot coating is 100-140°C, and the drying time is 4-5h.
7. The method for preparing a porous ceramic substrate electrochemical gas sensor according to claim 1, characterized in that: In step (4), the nafion solution pretreatment method is as follows: the nafion solution is mixed with one of glycerol, ethylene glycol, ionic liquid, neopentyl glycol ester, and DMF in a volume ratio of 1:1 to obtain a pretreated nafion solution.
8. A porous ceramic substrate electrochemical gas sensor prepared according to the method for preparing a porous ceramic substrate electrochemical gas sensor according to any one of claims 1 to 7.
9. Use of the porous ceramic substrate electrochemical gas sensor according to claim 8 in detecting hydrogen.
Citation Information
Patent Citations
Preparation method of silicon carbide-silicon nitride porous composite ceramic
CN107353015A
YSZ (yttria-stabilized zirconia)-based mixed potential type H2S sensor with La2NiO4 used as sensitive electrode and method for preparing YSZ-based mixed potential type H2S sensor
CN107655948A
Preparation method of porous membrane layer, electrochemical sensor and preparation method
CN110044982A
Ceramic surface modification materials and methods of use thereof
CN113195112A
Electrode substrate of solid electrochemical gas sensor and manufacturing method of sensor
CN114441619A